2006
DOI: 10.1118/1.2161403
|View full text |Cite
|
Sign up to set email alerts
|

Wall correction factors, , for thimble ionization chambers

Abstract: The EGSnrc Monte Carlo user-code CSnrc is used to calculate wall correction factors, Pwall, for thimble ionization chambers in photon and electron beams. CSnrc calculated values of Pwall give closer agreement with previous experimental results than do the values from the standard formalism used in current dosimetry protocols. A set of Pwall values, computed at the reference depth in water, is presented for several commonly used thimble chambers. These values differ from the commonly used values by up to 0.8% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 33 publications
10
52
0
1
Order By: Relevance
“…In order to obtain a consistent conversion of absorbed dose in the chamber cavity to absorbed dose in water ͑i.e., the product of all perturbation factors must be equal to the ratio of absorbed dose in water to absorbed dose in the chamber͒, a series of scoring volumes is defined starting at the fully modeled chamber and ending at a small volume of water placed at the centroid of the chamber. Similar to previous studies, [23][24][25] a series of cavity doses is defined as follows: with liquid water ͑density of 1.000 g / cm 3 ͒, and ͑7͒ D w,point : absorbed dose in a 1 mm radius sphere of water placed at the centroid of the chamber and representing absorbed dose at a point in water at the location of measurement.…”
Section: Iib Monte Carlo Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain a consistent conversion of absorbed dose in the chamber cavity to absorbed dose in water ͑i.e., the product of all perturbation factors must be equal to the ratio of absorbed dose in water to absorbed dose in the chamber͒, a series of scoring volumes is defined starting at the fully modeled chamber and ending at a small volume of water placed at the centroid of the chamber. Similar to previous studies, [23][24][25] a series of cavity doses is defined as follows: with liquid water ͑density of 1.000 g / cm 3 ͒, and ͑7͒ D w,point : absorbed dose in a 1 mm radius sphere of water placed at the centroid of the chamber and representing absorbed dose at a point in water at the location of measurement.…”
Section: Iib Monte Carlo Methodsmentioning
confidence: 99%
“…For ionization chambers, this perturbation is caused by several factors, which can be classified as follows: ͑1͒ The presence of structural and electronic components, ͑2͒ a detection material with a different atomic composition than water, ͑3͒ a detection material with different density than water, and ͑4͒ a detector volume that is finite. As formalized in reference dosimetry protocols, 11-14 and more recent publications, [23][24][25] ionization chamber perturbation factors represent each of these effects individually ͑although in practice, they are correlated͒ when converting absorbed dose to the chamber to absorbed dose to water. The presence of the chamber stem, central electrode, and wall will cause the charged-particle fluence to change in terms of quality and quantity due to attenuation and scatter in these components.…”
Section: Iia Formalism Of Absorbed Dose At a Pointmentioning
confidence: 99%
“…Therefore, the difference in the k Q factors for the three protocols appears due to the difference between the perturbation factors obtained by a semi‐analytic approach and MC calculations. Several studies14, 15, 16, 36 have compared individual perturbation correction factors obtained using MC calculations for cylindrical chambers with those obtained using a semi‐analytic approach, such as that used in IAEA TRS‐398 and AAPM TG‐51. For a 60 Co beam, the value of the replacement factor derived from MC calculations by Wang and Rogers17 was 0.5% higher than the AAPM TG‐51 value and approximately 1% higher than the IAEA TRS‐398 value.…”
Section: Discussionmentioning
confidence: 99%
“…For a 60 Co beam, the value of the replacement factor derived from MC calculations by Wang and Rogers17 was 0.5% higher than the AAPM TG‐51 value and approximately 1% higher than the IAEA TRS‐398 value. Buckley and Rogers16 and Muir and Rogers14 showed that the values of the wall correction factors derived from MC calculations for a wall material comprising PMMA, such as that found in PTW 30013, a wall material comprising C‐552, such as that found in Exradin A12, and a wall material comprising POM, such as that found in IBA FC65‐P, differed by −0.2%–0.4% from the AAPM TG‐51 value. However, in this study, the k Q factors for the three protocols agreed within a relative uncertainty of 1.0% in the k Q values for IAEA TRS‐398 and JSMP 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation